Analisis Kelayakan Usaha Toko Bahan Bangunan (Keramik) Di Desa Bambe Kecamatan Driyorejo Kabupaten Gresik - Dimas Tri Cahyono Putra; I Made Suparta (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to analyze the acceptance, profits and feasibility of a 6 ceramic shop business in Bambe Village, Driyorejo District, Gresik Regency. This research uses descriptive qualitative research. Data was collected through interviews, and the analytical methods used in this research were fixed costs, variable costs, total costs, revenues, profits and business feasibility and using calculations of Return On Investment (ROI), Revenue Cost Ratio (R/C) and Benefit Cost Ratio (B/C Ratio). The results obtained from this research are by using calculations of Return On Investment (ROI), Revenue Cost Ratio (R/C) and Benefit Cost Ratio (B/C Ratio) resulting in high figures obtained in ROI, B/C Ratio, R/ The C Ratio exceeds the predetermined number or value. The results show that the 6 ceramic shop business in Bambe Village, Driyorejo District, Gresik Regency is worthy of business and development.